NARASI PROSES BERKARYA PENULIS SLASH PAIRING - Lusia Kusumaratih Pramudyawardani; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The dominance of heteronormative values in indonesian society causes limited impressions and information about alternative sexuality messages in the mass media. But even so, for fans who love slash pairing fanfiction, this is not an obstacle in voicing their voices that are forced to close. They express themselves, voicing stories that have been silenced through a work of fiction about their idols in the form of fanfiction slash pairing. This is what is considered important to study, about how the journey story of female fans who write stories about alternative sexuality amid the dominance of heteronormative values around them. Therefore, this study aims to analyze the stories of female fans who write slash pairing fanfiction. The results of this study show that the value of heteronormativity still influences female fans in writing slash pairing fanfiction. When female fans do things that go against the value of heteronormativity, they will be stigmatized negatively by those closest to them and society because they are considered to have committed despicable and sinful acts, so female fans must hide their identities and even stop their writing activities that become a place to express and voice their opinions.